Non-invasive immuno-metabolic cardiac inflammation imaging using hyperpolarized magnetic resonance - Lewis, A; Miller, J; Lau, A; Curtis, M; Rider, O; Choudhury, R; Neubauer, S; Cunningham, C; Carr, C; Tyler, D (American Heart Association, 2018)
Rationale: Current cardiovascular clinical imaging techniques offer only limited assessment of innate immune cell driven inflammation, which is a potential therapeutic target in myocardial infarction (MI) and other diseases. Hyperpolarized magnetic resonance (MR) is an emerging imaging technology that generates contrast agents with 10-20,000 fold improvements in MR signal, enabling cardiac metabolite mapping. Objective: To determine whether hyperpolarized MR using [1-13C]pyruvate can assess the local cardiac inflammatory response following MI. Methods and Results: We performed hyperpolarized [1-13C]pyruvate MR studies in small and large animal models of MI as well as in macrophage-like cell lines and measured the resulting [1-13C]lactate signals. MI caused intense [1-13C]lactate signal in healing myocardial segments at both day 3 and 7 following rodent MI, which was normalised at both timepoints following monocyte/macrophage depletion. A near-identical [1-13C]lactate signature was also seen at day 7 following experimental MI in pigs. Hyperpolarized [1-13C]pyruvate MR spectroscopy in macrophage-like cell suspensions demonstrated that macrophage activation and polarization with lipopolysaccharide almost doubled hyperpolarized lactate label flux rates in vitro; blockade of glycolysis with 2-deoxyglucose in activated cells normalised lactate label flux rates and markedly inhibited the production of key pro-inflammatory cytokines. Systemic administration of 2-deoxyglucose following rodent MI normalised the hyperpolarized [1-13C]lactate signal in healing myocardial segments at day 3 and also caused dose dependent improvement in IL-1β expression in infarct tissue without impairing production of key 'reparative' cytokines. Cine MRI demonstrated improvements in systolic function in 2-DG treated rats at 3 months. Conclusions: Hyperpolarized MR using [1-13C]pyruvate provides a novel method for the assessment of innate immune cell driven inflammation in the heart following MI, with broad potential applicability across other cardiovascular disease states and suitability for early clinical translation.